Incorporating Community Governance: Planning Sustainable Energy Security - Costello, Diane (Common Ground Publishing, 2011)
Climate change has focussed global attention on reducing greenhouse gas (GHG) emissions, particularly through energy efficient technological innovation. In Australia energy policy incentives include increasing the contribution of renewable energy sources along with energy efficient behaviours. In Western Australia an Energy Utility has embraced the principle of community engagement to inform corporate strategies toward sustainable green energy visions. This paper evaluates the process of citizen involvement in promoting community acceptance of green energy technologies at the community level. This qualitative study examines the role of community governance in planning the sustainable energy needs of regional communities. While it is promising to observe the emergence of flexible institutional responses to community energy visions, this energy governance network is a work in progress as it struggles to gain community consensus to site a small community-owned wind farm. To address community polarisation over the costs and benefits of community energy, attention must be paid to issues of inclusive representation along with mechanisms of accountability that assesses the social and economic impacts of green energy initiatives. This study highlights that an effective governance process would incorporate the principles of sustainability, procedural and distributive justice to enhance community transitions toward a more environmentally benign economy and electricity system.